Solid waste management evaluation in Lantowua final processing place’s work area, Bombana Regency, 2021 - rahma, sitti (BKM Public Health and Community Medicine, 2021)
Background: Solid waste is still a problem for health and the environment. The increase of solid waste is in line with the growth in the population, and the community needs to encourage the application of 3R principles. The government has arranged this systematically, thus making the involvement of various stakeholders and communities crucial to implementing these principles. Purpose: This research aimed to evaluate the solid waste management implementation in Lantowua Final Processing Place’s work area, Bombana Regency. Methods: This was a qualitative case study approach in Lantowua Final Processing Place’s work area, including 16 informants. Data collection were through interviews, observation, and document studies. Data analysis used thematic analysis. Results and Discussion: The human resources, funds, and facilities input indicators were insufficient for program needs. The process indicators had no reduce-reuse-recycle principle, no solid waste sorting, and low socialization in the community. The output target indicators for solid waste handling targets had not yet applied the 3R principles at the household and shopping centers level. Environmental services had not involved cross-sector in solid waste management. Lack of contribution to the development of TPS3R and Solid Waste Banks, monitoring and testing of landfill leachate never been done. Conclusion: Solid waste management had been carried out but had not implemented the 3R principles at the household and community level. There was low cross-sectoral cooperation in solid waste handling and no effort to handle leachate at the landfill.